TREM2 signaling pathway in sepsis-induced acute lung injury: physiology, pathology, and therapeutic applications - Hong-Lei Shen; Jing He; Fei Lin (Frontiers in Medicine)
Sepsis emerges as a formidable and life-threatening condition, born from an unregulated immune response to infection, presenting a significant challenge to global health. A notable complication of sepsis is acute lung injury (ALI), marked by profound hypoxia, rampant inflammation, and the accumulation of fluid within the pulmonary system. ALI harbors the potential to escalate into acute respiratory distress syndrome (ARDS), thereby exacerbating the severity of sepsis. The triggering receptor expressed on myeloid cells 2 (TREM2), predominantly situated within various myeloid cell types, plays a pivotal role in the modulation of neurodegeneration, inflammation, neoplasms, and other pathologies. Recent investigations have illuminated TREM2's considerable involvement in septic lung injury; however, the precise mechanisms and therapeutic implications within this context demand further scrutiny. This article endeavors to elucidate the intricate interplay between sepsis, lung injury, and TREM2's role in immune modulation. It will furnish an overview of the TREM2 signaling pathway's functions and mechanisms in both physiological and septic lung injury scenarios, while also evaluating the current status and advancements in TREM2-targeted therapies.